Application of biomonitoring approaches to evaluate multimetal exposure among residents of Chennai – a preliminary study - Babu, Jayachelvi; Swamy, Anjli N; Aravindalochanan, Vigneswari; Sendhil, Saritha; R, Padma Priya (International Journal of Innovative Research and Scientific Studies, 2025)
Multimetal, naturally occurring elements, have a widespread distribution in the environment due to industrial, agricultural, and technological applications, which has raised concerns about potential health impacts. This study aimed to explore multimetal exposure in 100 adults aged 20-60 years in Chennai, using human biomonitoring techniques. Blood samples were analyzed for arsenic, cadmium, chromium, lead, and vanadium concentrations using ICP-MS, and matrix-matched certified reference material was used for quality control and assurance. Questionnaires were collected for exposure information. The limits of detection (LOD) for trace metals were: As 0.26, Cd 0.23, Cr 0.36, Pb 0.29, and V 0.29 µg/L, respectively. The Seronorm-certified reference values for whole blood trace metals showed accuracy between 96 - 100%. Geometric mean concentrations were: As 0.3, Cd 0.03, Cr 0.87, Pb 4.65, and V 0.23 µg/dL, correspondingly. Cadmium concentration was associated with socioeconomic status (p = 0.02). Smoking demonstrated an association with chromium (p = 0.012) and vanadium (p = 0.003). Furthermore, vehicular traffic was associated with cadmium (p = 0.005) and chromium (p = 0.004), and lead concentration was associated with water treatment (p = 0.051). This study provides evidence of multimetal exposure risks in Chennai residents. Further large-scale biomonitoring studies are warranted to elucidate exposure sources and health impacts.